(untitled) (Global Journal of Management and Business Research, 2020)
The purpose of this article is to assess the effect of competition on banking efficiency in developing countries and particularly some countries of the CEMAC during the period 2000- 2013 To achieve this our methodological approach is structured around two stages First we calculate the banking efficiency levels using the non-parametric input-oriented DEA method with variable returns to scales Second we assess the effect of competition as measured by the CR3 concentration ratio on efficiency levels using a Tobit model The results reveal a negative effect of competition on bank efficiency